Innovation Capacity in the Management System of Islamic Boarding School Education Institutions : Quality Test of Instruments through Exploratory and Confirmatory Factor Analysis - Pratama, Robin; Yaakob, Mohd Faiz Mohd; Hendra, Robi; Wulandari, Okky (Universitas Pendidikan Mandalika, 2024)
This study aims to test the validity and reliability of instruments measuring the variable of innovation capacity in the management system of Islamic boarding school education institutions in Jambi City. This research method employed a cross-sectional survey design with a quantitative approach. The sample size for this study consisted of 162 teachers (Ustad/Ustadzah) in Islamic boarding school education institutions. Quantitative data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using SPSS 23 and AMOS 18. The results of this study indicated that EFA identified five factor structures to construct the dimensions of Innovation Capacity (IC), namely Opportunity Exploration (OE), Idea Sustainability (IS), Idea Introduction (II), Idea Emergence (IE), and Idea Realization (IR). Meanwhile, these findings were verified and confirmed by CFA regarding the factorial validity analysis of the Innovation Capacity dimension from the EFA testing results. This study suggests that future innovation capacity instruments require further adjustment to enhance the level of reliability and the ability to explain differences related to the measured constructs within different contexts, cultures, and conditions.